The phenomenon of burnout among medical students - literature review - Martyna Nowińska; Magdalena Kozyra; Przemysław Raczkiewicz; Marlena Kaczerska; Natalia Śmiech; Joanna Milanowska (Kazimierz Wielki University, 2021)
Introduction: Burnout is characterised by a triad of emotional exhaustion, depersonalisation and a decreased sense of accomplishment. Distress during medical school can lead to burnout, with significant consequences, particularly if burnout continues into residency and beyond. There is a lot of research into burnout and the authors reviewed literature pertaining to medical student burnout, its prevalence, and its relationship to personal, environmental, demographic and psychiatric factors. The aim of the study: Paying attention to the correlation between academic lifestyle and occurrence burnout among medical students. Material and method: The research was done by the usage of the PubMed and Google Scholar articles about the topic of: burnout; stress; medical students; behaviour. Description of the state of knowledge: The educational process brings a considerable amount of stress to medical students that can influence mental health status and contribute to further professional burnout. According to various studies and definitions of occupational burnout, this phenomenon is observed in up to 76% of medical students. Research has identified associations between burnout and lifestyle health behaviours. Also relationship between the occurrence of burnout and suicide attempts has been demonstrated. In turn spirituality has been positively influence well-being and to prevent burnout. Summary: Undoubtedly, it is worth paying attention to the phenomenon of occupational burnout among students from the first years of medical studies. Universities should make efforts to reduce the risk of the occurrence and further development of burnout, which may have negative effects in the future work with the patient.